Keefektifan Konseling Teknik Positive Mental Time Travel untuk Menurunkan Tingkat Kecemasan Lansia - Irman Irman; Silvianetri Silvianetri; Fadilah Syafwar; Zubaidah Zubaidah; Putri Yeni; Zulfikar Zulfikar (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2022)
The dominant problem experienced by the elderly is the high level of anxiety which has an impact on the physical and psychological. This study aims to examine the effectiveness of positive mental time travel counseling techniques to reduce the level of anxiety in the elderly. The approach used is experiments, especially pretest & posttest control group design. The research subjects were the elderly at the Sabai Nan Aluih Nursing Home, which amounted to 20 people indicated experiencing anxiety in the high category. Subjects were divided into two groups, namely the experimental group and the control group. The experimental group received a positive mental time travel technique counseling intervention and the control group received a lecture intervention in the group. Data were collected using the Elderly Anxiety Scale, and analyzed using a different test independent samples t test through the SPSS computer program Release 20. The results showed that; (1) there is a difference in the level of anxiety of the elderly who are given positive mental time travel techniques with the elderly who are not given positive mental time travel technique counseling, and (2) the counseling of positive mental time travel techniques is effective in reducing the level of anxiety of the elderly. It is recommended for practitioners to use positive mental time travel counseling techniques to reduce the level of anxiety in the elderly in order to realize the mental health of the elderly.